Určování obsahu chlorofylu ve vybraných travních společenstvech krkonošské tundry na základě terénní spektroskopie a leteckých hyperspektrálních dat - Pinlová, Gabriela (Univerzita Karlova, Přírodovědecká fakulta, 2022)
The thesis focuses on the determination of chlorophyll content from hyperspectral data in grass communities in the arctic-alpine tundra in the Krkonoše Mountains, namely Nardus stricta, Molinia caerulea, Calamagrostis villosa, and Deschampsia cespitosa. Leaf chlorophyll content (LCC) was measured using two methods - spectrophotometric destructive determination in the laboratory, and the LCC assessed non-destructively by fluorescence portable chlorophyll meter CCM-300. Leaf area index (LAI) values for canopy chlorophyll content (CCC) retrieval were also acquired by destructive biomass sampling and indirectly using LAI-2200C. Relationships were established between the LCCs, LAI, CCCs, and vegetation indices (VI) calculated from respective spectra, i.e. leaf level spectra acquired with contact probe coupled with an ASD FieldSpec4 Wide-Res spectroradiometer, canopy level spectra measured by the spectroradiometer and extracted from hyperspectral images (HSI) acquired by Headwall Nano- Hyperspec® mounted on the DJI Matrice 600 Pro drone. Chlorophyll content maps were created based on the results of multiple stepwise linear regression applied to HSI. For the model, derived from the non-destructive data sampling and used for the LCC map, a RMSE of 66.55 mg/m2 was achieved. Keywords: leaf chlorophyll. Diplomová práce se zaměřuje na stanovení obsahu chlorofylu z hyperspektrálních dat v travních společenstvech krkonošské tundry, jmenovitě smilky tuhé (Nardus stricta), bezkolence modrého (Molinia caerulea), třtiny chloupkaté (Calamagrostis villosa) a metlice trsnaté (Deschampsia cespitosa). Hodnoty obsahu chlorofylu na úrovni listu (LCC) byly naměřeny destruktivně spektrofotometricky v laboratoři a nedestruktivně chlorofylmetrem CCM-300. Hodnoty indexu listové plochy (LAI) pro výpočet obsahu chlorofylu na úrovni porostu (CCC) byly stanoveny taktéž destruktivně na základě odběru biomasy a nedestruktivně přístrojem LAI-2200C. Práce se věnuje popisu vlastností naměřených hodnot LCC, LAI a CCC a jejich korelací s vegetačními ...